Assessment of Relationship Between Sleep Position and Nasal Septum Deviation with Polysomnographic Data - Şahin, Ender; Selim İntepe, Yavuz; Cengiz, Ceyhun; Dağıstan, Hakan; Haberal Can, Ilknur; Çiftçi, Bülent (ENT Updates, 2021)
Objective: The aim of this study was to investigate the relationship between septum deviation and sleeping position in patients with nasal septum deviation. Methods: The study included 25 patients with nasal septum deviation on the right side, 25 patients with septum deviation on the left side, and 25 patients without septum deviation as the control group. The polysomnography reports of these patients were assessed retrospectively, and the spans of rest in the right, left, and supine positions were evaluated. Results: The right side-lying time was significantly longer than the left side-lying time in the group with right side deviation (P < .01). In the group with left sided septal deviation, the left side-lying time was significantly longer than the right side-lying time (P < .01). There was no significant difference between the 2 side-lying periods (P = .118). Moreover, the ratio of sleep duration in the supine/non-supine position in the groups with deviation was significantly higher than that in the control group. Conclusion: The results of our study showed that patients with nasal septum deviation slept more in the supine position than those without deviation and slept more on the deviated side when sleeping in the non-supine position.